Rotavirus G and P types in children from Belém, northern Brazil, as determined by RT-PCR: occurrence of mixed P type infections - Mascarenhas, Joana D'Arc Pereira (1998)
Fifty-four group A rotavirus-positive stool samples, obtained from children aged less than three years during a longitudinal (December 1982 to March 1986) study in Belém, Brazil, were re-examined. The samples were tested by reverse-transcription and polymerase chain reaction to determine their G-type and P-type specificity. Only 17 (32 percent)of these rotavirus strains could be successfully G- and P-genotyped. While 10 (59 percent) of the 17 strains showed single G- and P-type specificity, the remaining belonged to single G- and mixed P-genotypes. Rotavirus strains P[8], G1 and P[4], G1 predominated, accounting for 29 percent and 18 percent of the typed strains respectively. Mixed P-type infections caused by rotaviruses classified as P[8]+P[4], G1 were identified in 23 percent. All but 3 of the 54 rotavirus strains displayed long genomic profiles, as demonstrated by the analysis of RNA by polyacrylamide gel electrophoresis. Most (70 percent ) rotavirus strains with single G- and P-type specificity were detected during the first year of life, whereas 5 (71 percent) of the seven mixed P-type infections occurred throughout the second or third year of age. Reinfections were noted in two children, both of them being infected with P[8]+P[4], G1 rotavirus strains when aged 20 months. The high proportion of untypeable rotavirus strains suggests that unusual types may be circulating in Belém. In addition, the occurrence of mixed P-type infections in our region indicates the potential for reassortment between different rotavirus genogroups. Monitoring of these rotavirus strains may have important implication in the context of future strategies of rotavirus vaccination in Brazil